Physiological Effects of Binaural Beats and Meditative Musical Stimulation - Elizabeth Hill; Christina Frederick (Undergraduate Research Journal for the Human Sciences, 2016)
The current study examined physiological effects of meditation music and binaural beats on humans, solo and in combination. A binaural beat is the presence of two separate auditory tones with equal amplitude and slightly differing frequencies (Goodin et al., 2012). Meditation music is often used with binaural beats to calm individuals (Chan et al., 2008). There is reason to believe binaural beats and meditative music impact human vital signs (Wahbeh et al., 2012). Heart rate, blood pressure, and oxygen saturation were recorded from 60 participants, tested individually, and randomly assigned to one of three listening groups: Beat + Music, Music Only, or Beat Only. Participants experienced their assigned auditory stimulation through headphones for 6 min. Physiological responses were recorded before and during auditory stimulation. A one- way ANOVA showed a significant difference in mean heart rate between listening groups (p = .046). Due to sample size limitations, a subsequent Tukey test (Abdi & Williams, 2010) could not identify the location of the significant difference. The largest difference in averages (at 9.05 bpm) existed between Beat Only and Music Only groups, therefore, indicating this as the location of the significant difference. No significant difference was found between listening groups in blood pressure (systolic: p = .937; diastolic: p = .954) or oxygen saturation (p = .752). It is recommended future studies in this domain incorporate larger sample sizes to ensure statistical sensitivity.
Keywords: Meditation; music